Village Fund Management As A Catalyst For Prosperity: A Perspective From Sumber Kramat Village, Tongas District, Probolinggo Regency - Maria Ulfa Hosen; Moh. Rasidi (SOUTHEAST ASIA JOURNAL oF GRADUATE OF ISLAMIC BUSINESS AND ECONOMICS, 2025)
Village Fund Management (VFM) is an initiative aimed at reducing development disparities between villages, particularly in improving community welfare. In this context, transparency from village officials to the public is essential. Based on this background, this study aims to analyze how the management of Village Funds in Sumber Kramat Village can positively impact the improvement of community welfare and to identify factors that influence the effectiveness of Village Fund utilization. Furthermore, this research focuses on Village Fund management that actively involves the community, with the goal of providing recommendations for a more transparent, efficient, and sustainable Village Fund management system. This study employs a qualitative approach or field study method. The results indicate that the management of Village Funds for health programs in Sumber Kramat Village has had a positive impact on the quality of life of the community, particularly through the establishment of the Polindes (village clinic), Posyandu (integrated health service post) programs, maternal health counseling, and adolescent induction programs. These programs have improved access to basic health services, maternal and child health, and raised community awareness of healthy lifestyles. The empowerment of health cadres has strengthened community independence in maintaining their health. Although youth participation in some programs remains low, the management of Village Funds has successfully reduced transportation and medical costs while enhancing community productivity. This effective management in the health sector can serve as a model for other villages to improve community welfare.